Assessment of the Existing Public Housing Stock Supplied in Awka Capital Territory, Awka, Anambra State - I. U. Okafor (INTERNATIONAL JOURNAL OF ENGINEERING AND MODERN TECHNOLOGY, 2026)
The research was aimed at assessing the existing public housing stock supplied in Awka Capital Territory, Anambra State. It further determines the qualities and quantities of housing typologies that are demanded and supplied in the public housing estates in Akwa. It established that there is a significant deficit in housing supply, also, identified the housing typologies that are more in general demand. It further recommended that the housing typologies that are more demanded should be adopted for future public housing development scheme in Anambra State.